Validation of the EBMT Risk Score for South Brazilian Patients Submitted to Allogeneic Hematopoietic Stem Cell Transplantation. (12th December 2013) - Pitombeira, Beatriz Stela; Paz, Alessandra; Pezzi, Annelise; Amorin, Bruna; Valim, Vanessa; Laureano, Alvaro; Wieck, Andrea; Rigoni, Lisandra; Ottoni, Érica; Fisher, Gustavo; Daudt, Liane; Silla, Lucia
Abstract : Background . Allogeneic hematopoietic stem cell transplantation (HSCT) is still associated with a high transplant-related mortality rate. In 2009, the EBMT risk score was validated as a simple tool to predict the outcome after allogeneic HSCT for acquired hematological disorders. Objectives . The aim of this study was to validate the applicability of the EBMT risk score for allogeneic HSCT on South Brazilian patients. Methods . A retrospective observational study was performed based on patients' records and data base at Hospital de Clínicas de Porto Alegre, including all allogeneic transplants for malignant and severe aplastic anemia from 1994 to 2010. Patients were categorized according to EBMT risk score and overall survival (OS). Nonrelapse mortality (NRM) and relapse rate (RR) were analyzed. Results . There were 278 evaluable patients. OS, NRM, and RR at five years median followup were 48.7%, 40.7%, and 30.7%, respectively. The OS was 81.8% for risk score 0 and 0% for score 6 (P < 0.001 ), and NRM was 13.6% and 80% for risk scores 0 and 6, respectively (P = 0.001 ). Conclusion . The EBMT risk score can be utilized as a tool for clinical decision making before allogeneic HSCT for malignant hematological diseases and severe aplastic anemia at a single center in Brazil.